If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5a + -2)(6a + -4) = 0 Reorder the terms: (-2 + 5a)(6a + -4) = 0 Reorder the terms: (-2 + 5a)(-4 + 6a) = 0 Multiply (-2 + 5a) * (-4 + 6a) (-2(-4 + 6a) + 5a * (-4 + 6a)) = 0 ((-4 * -2 + 6a * -2) + 5a * (-4 + 6a)) = 0 ((8 + -12a) + 5a * (-4 + 6a)) = 0 (8 + -12a + (-4 * 5a + 6a * 5a)) = 0 (8 + -12a + (-20a + 30a2)) = 0 Combine like terms: -12a + -20a = -32a (8 + -32a + 30a2) = 0 Solving 8 + -32a + 30a2 = 0 Solving for variable 'a'. Factor out the Greatest Common Factor (GCF), '2'. 2(4 + -16a + 15a2) = 0 Factor a trinomial. 2((2 + -5a)(2 + -3a)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(2 + -5a)' equal to zero and attempt to solve: Simplifying 2 + -5a = 0 Solving 2 + -5a = 0 Move all terms containing a to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -5a = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -5a = 0 + -2 -5a = 0 + -2 Combine like terms: 0 + -2 = -2 -5a = -2 Divide each side by '-5'. a = 0.4 Simplifying a = 0.4Subproblem 2
Set the factor '(2 + -3a)' equal to zero and attempt to solve: Simplifying 2 + -3a = 0 Solving 2 + -3a = 0 Move all terms containing a to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3a = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3a = 0 + -2 -3a = 0 + -2 Combine like terms: 0 + -2 = -2 -3a = -2 Divide each side by '-3'. a = 0.6666666667 Simplifying a = 0.6666666667Solution
a = {0.4, 0.6666666667}
| 10n-6(10+n)-3= | | 2x-17=80-5x | | 15z-4(2+z)-2z= | | m-2=2m | | 6x-2-9x=1 | | 3x+4=-(X-20) | | 5x+31-81=(2x-5)(2x-5) | | 177-2x=34x+21 | | 4=t+6 | | 5+4(s-3t)= | | -4-(-4)= | | 1-3= | | 625=3m^2 | | 2x+12=-15-7x | | 0-5= | | 15z+4(-2+z)-2z= | | 1+12=45+x | | x^6=215 | | 5x+105=(3x+13)(3x+13) | | 156-6x=5x+24 | | x^6-34=181 | | x-36=-46 | | 9p+3=8+8p | | 72=5t-13t | | 3(3p-1)-(p+7)= | | 5x+y=30 | | 4x-16=40 | | 2x+7=49+4x | | 4(2x-5)= | | 9b-2b= | | -3x=4-(-8) | | y=2(6+1)+5(3+2) |